Detection of equine herpesvirus 1 genome 1B in Argentina - Martínez, J. P. (2006)
To determine the genomic variation of equine herpesviruses (EHVs) isolated in Argentina between 1979 and the first half of 2004, DNA sequences from all 69 strains isolated were analysed. Sixty strains were recovered from aborted fetuses, one from leucocyte-rich plasma from a horse with respiratory signs and eight from cases of neonatal disease. The DNA was extracted from rabbit kidney epithelial (RK13) cells infected with each strain and digested with three restriction endonucleases (BamHI, Bg/II and KpnI). Two strains could be differentiated using BamHI restriction and were assigned to the EHV-1 1B prototype group. Only one of these two strains was typed EHV-1 1B with Bg/II. DNA digestion with KpnI was ineffective. The results obtained in this study demonstrate that the EHV-1 1B genome has been present in Argentina since at least 1996. The finding of two strains with this electropherotype suggests that there is genomic heterogeneity among Argentinian isolates.